QUO VADIS: URGENSI PENGATURAN PEMBIAYAAN PENEMPATAN PEKERJA MIGRAN INDONESIA - Claudia, Winda; Dwijayanthi, Putri Triari (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 4 (2023), 2023)
The purpose of this study is to analyze the urgency of arranging financing placement of Indonesian Migrant Workers and the implications of the absence of such regulation. This study was using normative research methods with a statutory and conceptual approaches as well as qualitative analysis.  The result of the study obtained are that although the placement of Migrant Workers in Indonesia has been regulated in a number of arrangements, there is still a legal voids and conflicting norms that can be found in Law 18 of 2017 and PerBP2MI No 9 of 2020 concerning the placement financing of Indonesian Migrant Workers. These requirements must be fulfill based on different arrangements regarding protection for Indonesian Migrant Workers. The absence of these regulations has implications for several things, including the non-realization of legal certainty and legal protection, the potential for violating the principles of protection for Indonesian Migrant Workers, causing overcharging practices, as well as the occurance of criminal acts and human trafficking. Therefore, it has become an urgency for the government to immediately take steps to establish related arrangements regarding the placement financing of Indonesian Migran Workers.